Diagnosis and management of PNH: Review and recommendations from a Belgian expert panel. (23rd October 2018) - Devos, Timothy; Meers, Stef; Boeckx, Nancy; Gothot, Andre; Deeren, Dries; Chatelain, Bernard; Chatelain, Christian; Devalet, Bérangère
Abstract: Despite its considerable morbidity and mortality, paroxysmal nocturnal haemoglobinuria (PNH) is still underdiagnosed. Patients with PNH can suffer from cardiovascular, gastrointestinal, neurological or haematological symptoms and refer to several specialists. The aim of this paper is to review the diagnosis and the management of PNH patients, with the primary focus on identifying high‐risk groups. Additionally, the implementation and prognostic value of the defined high‐risk groups will be commented on and the management of PNH patients is discussed from a Belgian perspective. Finally, based on the available data, recommendations are provided. Eculizumab is a potent C5 complement inhibitor and reduces intravascular haemolysis and thrombosis in PNH patients and improves their quality of life. As thrombosis is the main cause of death in PNH patients, identifying high‐risk PNH patients in need of therapy is essential. Currently, novel complement inhibitors are in development and the first data seem promising. Another challenge in PNH is to identify new markers to assess the thrombotic risk to achieve a better risk‐based prophylactic anti‐thrombotic management. Finally, because of the low prevalence of the disease, PNH patients should be included in the prospective PNH registry, which will offer new insights on the natural course of the disease and the impact of treatment of PNH.